1944
DOI: 10.1021/ie50413a025
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Methyl Acetoxypropionate:Reaction of Lactic Acid with Methyl Acetate

Abstract: EFFICIENTand inexpensive methods of converting lactic acid (27, 28, 29) into its diester, methyl «-acetoxypropionate (I), are highly desirable since on pyrolysis methyl «-acetoxypropionate yields methyl acrylate and acetic acid (5, 12, 21, 22, 29). The preparation of methyl acrylate, an important synthetic rubber (1, 6, 9,10, 28,24,80,85) and resin (18) intermediate, by pyrolysis of the acetyl derivative (I) of methyl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1945
1945
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…The rst encounter of LA usage to produce AA is found in a 1935 paper 78 by Burns et al and this was followed in the 1940s with papers by Fisher and co-workers [79][80][81][82][83] and a patent led in 1949 by Atwood. 84 Generally, an alkyl lactate is converted into its corresponding alkyl acrylate via pyrolysis of an alkyl 2-acetoxypropionate intermediate with the formation of acetic acid as a by-product.…”
Section: Dehydration To Acrylic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…The rst encounter of LA usage to produce AA is found in a 1935 paper 78 by Burns et al and this was followed in the 1940s with papers by Fisher and co-workers [79][80][81][82][83] and a patent led in 1949 by Atwood. 84 Generally, an alkyl lactate is converted into its corresponding alkyl acrylate via pyrolysis of an alkyl 2-acetoxypropionate intermediate with the formation of acetic acid as a by-product.…”
Section: Dehydration To Acrylic Acidmentioning
confidence: 99%
“…82 The acetoxy intermediate is made by contacting an alkyl lactate with acetic anhydride, 79,84 or alternatively from lactic acid with acetic acid and an entraining agent followed by esterication or with methyl acetate directly. 80 Werpy et al continued on this path, but proposed an azeotropic distillation setup with an acid catalyst to prepare the precursor from LA and acetic acid before subjecting the precursor to pyrolysis. In this last step, a weak acidic catalyst can be added.…”
Section: Dehydration To Acrylic Acidmentioning
confidence: 99%
“…Toxic concentrations of metals resulting from the corrosion of the equipment have been encountered frequently in experimental work (25,54).…”
Section: Crude Lactic Acid As Starting Materialsmentioning
confidence: 99%
“…tion of methyl lactate in high yield by conventional methods is unusually difficult because methyl lactate distills azeotropically with water but methanol does not, and methyl lactate is readily hydrolyzed (25). Although esterification of lactic acid with methanol is troublesome, this operation is important because methyl lactate can be converted readily into higher lactic esters by alcoholysis (5) or into methyl acrylate by pyrolysis of its acetyl derivative (5,29).…”
mentioning
confidence: 99%
“…Previous communications (5,20) from this laboratory have shown that methanol reacts readily with condensation polymers of lactic acid, methyl lactate is readily volatilized in a stream of methanol vapor, and methyl lactate and w-ater distill azeotropically. These facts seemed to warrant an investigation of the preparation and removal of methyl lactate from aqueous solutions of lactic acid by passing methanol vapor through the solution.…”
mentioning
confidence: 99%